2003
DOI: 10.1111/j.1572-0241.2003.07234.x
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of lactulose breath testing correlates with symptom improvement in irritable bowel syndrome: a double-blind, randomized, placebo-controlled study

Abstract: OBJECTIVE:We have recently found an association between abnormal lactulose breath test (LBT) findings and irritable bowel syndrome (IBS). The current study was designed to test the effect of antibiotic treatment for IBS in a doubleblind fashion. METHODS:Consecutive IBS subjects underwent an LBT with the results blinded. All subjects were subsequently randomized into two treatment groups (neomycin or placebo). The prevalence of abnormal LBT was compared with a gender-matched control group. Seven days after comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
444
5
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(465 citation statements)
references
References 27 publications
10
444
5
6
Order By: Relevance
“…There are market-driven needs for robust and sensitive sensors to monitor the concentration of hydrogen under humid ambient in the application of hydrogen fuel cell vehicles and hydrogen breath test in medical dioagnosis. [4][5][6]21,33 Methods to mitigate the effects of absorbed water molecules would be a major step toward expanding these applications. Kumar et al investigated effects of various polymer encapsulations including poly(methyl methacrylate) (PMMA) on selective hydrogen sensing of nanocrystalline In 2 O 3 -doped SnO 2 thin film sensors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are market-driven needs for robust and sensitive sensors to monitor the concentration of hydrogen under humid ambient in the application of hydrogen fuel cell vehicles and hydrogen breath test in medical dioagnosis. [4][5][6]21,33 Methods to mitigate the effects of absorbed water molecules would be a major step toward expanding these applications. Kumar et al investigated effects of various polymer encapsulations including poly(methyl methacrylate) (PMMA) on selective hydrogen sensing of nanocrystalline In 2 O 3 -doped SnO 2 thin film sensors.…”
mentioning
confidence: 99%
“…[1][2][3] In addition, reliable and accurate hydrogen sensor is required in medical diagnosis applications including hydrogen breath test to detect carbohydrate malabsorption and SIBO (small intestinal bacterial overgrowth) of patients. [4][5][6] Among semiconductor-based hydrogen sensors, various types of wide bandgap GaN (3.4 eV) thin film or nanostructured devices contacted with Pt-or Pd-gate metals are attractive for their robustness and wide operating temperature. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, the availability of piezoelectric AlGaN/GaN heterostructures enables the design of transistor-based sensors with enhanced sensitivity.…”
mentioning
confidence: 99%
“…Moreover, some studies showed that short course of antibiotic therapy resulted in significant improvement in GI symptoms of such patients (6). In a double blind clinical trial, neomycin resulted in 25% improvement among the results of lactulose breath test in comparison with that of placebo, and this drug was more effective in relieving clinical symptoms, although its usage was abandoned due to systemic absorption and side effects (18)(19)(20). Accordingly, in another study rifaximin, a non-absorbable antibiotic was more efficacious than placebo to treat bloating; although only 60% of participants in this study fulfilled the Rome II criteria to diagnose IBS and no one suffered through lactulose breath test (13).…”
Section: Discussionmentioning
confidence: 99%
“…Altered gastrointestinal motility and sensation, changed activity of the central nervous system, and increased sympathetic drive and immune activation may be interpreted as consequences of the host response to SIBO [16]. To further support abnormal enteric flora as the contributing cause of IBS, two recent studies have shown that metronidazole [29] and neomycin [30] are both able to cause a significant symptomatic improvement in this condition.…”
Section: Small Bowel Bacterial Overgrowthmentioning
confidence: 99%